ANALYSIS OF CHANGES IN THE FOREIGN LANGUAGE LEXICON USED BY THE MILLENNIAL GENERATION IN THE X APPLICATION IN INDONESIA - Moh Fikri Taufiqul Haq; Adityawan Hendratno; Mohammad Nawfal Arfa; Abdullah Faqih Amanullah; Endang Sholihatin (Media Inovasi Pendidikan dan Publikasi, 2024)
The language lexicon that has changed in the X application is more widely used by the millennial generation. The users of the X application, who are mostly from the millennial generation, now tend to use this variety of language not only in socializing through the application, but also in their daily lives. For example, the word